2018
DOI: 10.1101/397620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome Scale Epigenetic Profiling Reveals Five Distinct Subtypes of Colorectal Cancer

Abstract: BACKGROUND:Colorectal cancer is an epigenetically heterogeneous disease, however the extent and spectrum of the CpG Island Methylator Phenotype (CIMP) is not clear.RESULTSAn unselected cohort of 216 colorectal cancers clustered into five clinically and molecularly distinct subgroups using Illumina 450K DNA methylation arrays. CIMP-High cancers were most frequent in the proximal colons of female patients. These dichotomised into CIMP-Hl and CIMP-H2 based on methylation profile which was supported by over repres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This panel has been widely utilised and provides a readily available platform to indicate the methylation status of large numbers of samples. Recent studies that have utilised genome-wide methylation arrays have confirmed that those cancers with the most frequent and widespread methylation do significantly correspond with the BRAF mutation and MLH1 methylation [51, 52]. Methylation was observed to occur as a continuum at several sites; however, 4 and 5 distinct methylation-based clusters were identified [51, 52], and cancers with the most methylated genomes not only were BRAF mutant and MSI but also classified as CIMP-high using the more recent CIMP-denoting markers [50] which supports the utility of this panel.…”
Section: The Braf V600e Mutation In Colorectal Cancermentioning
confidence: 99%
“…This panel has been widely utilised and provides a readily available platform to indicate the methylation status of large numbers of samples. Recent studies that have utilised genome-wide methylation arrays have confirmed that those cancers with the most frequent and widespread methylation do significantly correspond with the BRAF mutation and MLH1 methylation [51, 52]. Methylation was observed to occur as a continuum at several sites; however, 4 and 5 distinct methylation-based clusters were identified [51, 52], and cancers with the most methylated genomes not only were BRAF mutant and MSI but also classified as CIMP-high using the more recent CIMP-denoting markers [50] which supports the utility of this panel.…”
Section: The Braf V600e Mutation In Colorectal Cancermentioning
confidence: 99%
“…2,9 Despite the suggestion, serrated pathway CRCs lack methylation of Wnt pathway genes. 72 Therefore, the molecular mechanism regulating Wnt activation in BRAF V600E -driven carcinogenesis has remained unresolved. Fascin1 is upregulated early in SSLs and our data show fascin1's direct role in Wnt activation suggesting a role for fascin1 in the initiation of serrated pathway carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…One in twenty has the risk of developing CRC during their lifetime (Bardhan et al, 2013). CRC is characterized by certain genetic and epigenetic changes that induce proliferative activity and inhibit apoptosis (Fennell et al, 2018). Activating proto-oncogenes or de-activating some tumor suppressor genes can lead to cancer (Munteanu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%